2004
DOI: 10.4049/jimmunol.172.12.7408
|View full text |Cite
|
Sign up to set email alerts
|

Increased and Long-Term Generation of Dendritic Cells with Reduced Function from IL-6-Deficient Bone Marrow

Abstract: The importance of IL-6 in dendritic cell (DC) development and function has not been well defined. To establish the role of IL-6, we studied bone marrow-derived DC (BMDC) and freshly isolated splenic DC from IL-6−/−-transgenic mice. We found that although IL-6−/− bone marrow had a similar composition to that of wild-type (WT) mice, it generated up to 10 times more DC when cultured in GM-CSF. The difference persisted even when IL-6−/− and WT bone marrow were cultured together, excluding the possibility that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 40 publications
2
30
1
Order By: Relevance
“…We found that LPS increased the alloproliferation in all groups (Fig. 5B), which was consistent with our previous findings showing that IL-6 increases the allostimulation of both bone marrow and freshly isolated splenic DCs (22). Notably, though, liver myeloid DCs from BDL-treated mice remained significantly more stimulatory.…”
Section: Lps Further Enhances the Function Of Liver Myeloid Dcs From supporting
confidence: 81%
“…We found that LPS increased the alloproliferation in all groups (Fig. 5B), which was consistent with our previous findings showing that IL-6 increases the allostimulation of both bone marrow and freshly isolated splenic DCs (22). Notably, though, liver myeloid DCs from BDL-treated mice remained significantly more stimulatory.…”
Section: Lps Further Enhances the Function Of Liver Myeloid Dcs From supporting
confidence: 81%
“…Neutrophils are the main source of early IFN-␥ production critical for activation of NK cells. Furthermore, IL-6 also has complex differential effects on differentiation and activation of dendritic cells and macrophages (49,50). Thus, the overt production of IL-6 may have lead to the deleterious consequence of lack of sufficient recruitment of inflammatory cell types in the systemic compartments of pregnant ST-infected hosts.…”
Section: Discussionmentioning
confidence: 99%
“…2B-D, IL-1b production was also elevated in DCs at 12 h post-isc treatment (p = 0.014); at 24 h, IL-12(p40) and TNF-a were released at significantly higher levels by isc DCs as compared with ctrl DCs (p , 0.0006); it should also be noted that TNF-a production has been shown to be subject to negative feedback inhibition via PGE upregulation as well as posttranscriptional mRNA destabilization, which may account for the decrease in TNF-a levels observed at 24 h compared with 12 h (38-41). IL-6 production is known to be increased following activation of TLR4, thereby leading to an inflammatory response (19,(42)(43)(44). This increase in IL-6 may thus serve to enhance the immune response initiated by DCs following isc injury.…”
Section: Results Isc Dcs Exhibit Increased Allostimulatory Activitymentioning
confidence: 99%